Sediaan Ekstrak Kering dari Maserat Kombinasi Herba Pegagan (Centella asiatica, [L.] Urban) dan Rimpang Temulawak (Curcuma xanthorrhiza, Roxb.) terhadap Peningkatan Daya Ingat Mencit Putih - Nuryani Nuryani; Suhartinah Suhartinah; Vivin Nopiyanti (Fakultas Farmasi Universitas Setia Budi, 2014)
Pegagan (Centella asiatica, [L.] Urban) gives positive effect on the cerebral nerve stimulation, and to smooth the blood transportation to the cerebral vessels. Wild ginger (Curcuma xanthorrhiza, Roxb) potentially protects the cell from oxidative damage and increases appetite. This study was aimed to find out effect of the combination of pegagan herb and wild ginger rhizome extracts in instant preparation to increase the memory. The step through passive avoidance method was used by analysis pretest and posttest latency time interval parameter from the length of time the mice needed to enter the dark compartment from bright compartment. The dose of 0.195 mg Ginkgo biloba as positive control, and 5.2 mg aerosol as negative control, combination of dry extract preparation at 2.6 mg (0.91 mg pegagan extract and 0.98 wild ginger extract), 5.2 mg (1.82 mg pegagan extract and 0.98 wild ginger extract), and 7.8 mg (2.73 mg pegagan extract and 2.94 wild ginger extract) doses. The data was analyzed using two-way ANOVA, followed by Tamhan’s T2 test. The result showed that the combination of macerated pegagan herb and wild ginger rhizome in dry extract preparation can improce memory of the white mice.